Pyroptosis in the lung and spleen of patients died from COVID-19. (14th November 2022) - Tong, Xin; Ping, Haiqin; Gong, Xiaoming; Zhang, Kai; Chen, Zhaojun; Cai, Caiyun; Lu, Zhiyan; Yang, Rongrong; Gao, Shicheng; Wang, Yunyun; Wang, Xinghuan; Liu, Liang; et al.
The purpose of this study was to investigate the expression of pyroptosis-related factors (NLRP3, IL-18, NF-κB, HMGB-1, and GSDMD) in patients who died of COVID-19. The expression levels of NLRP3, IL-18, NF-κB, HMGB-1, and GSDMD in lung and spleen tissues of the COVID-19 group and the control group were detected by tissue immunofluorescence. The control group includes lung tissues and spleen tissues of two patients who died unexpectedly without SARS-CoV-2 infection, and the COVID-19 group includes the lung and spleen tissues of three patients who died of SARS-CoV-2 virus infection. The positive rates of NF-κB, NLRP3, IL-18, and GSDMD in the lung tissues from the control group and COVID-19 group were 9.8% vs 73.4% ( p = 0.000), 5.5% vs 63.6% ( p = 0.000), 24.4% vs 76.2% ( p = 0.000), and 17.5% and 46.8% ( p = 0.000) respectively. The positive rates of NF-κB, NLRP3, IL-18, HMGB-1, and GSDMD in the spleen tissues from the control group and COVID-19 group were 20.6% vs 71.2% ( p = 0.000), 18.9% vs 72.0% ( p = 0.000), 15.2% vs 64.8% ( p = 0.000), 27.6% vs 69.2% ( p = 0.000), and 23% and 48.8% ( p = 0.000), respectively. The positive rates of SARS-CoV-2 spike protein in the CD68 positive cells of the lung and spleen in the control group and COVID-19 group were 2.5% vs 56.8% ( p = 0.000); 3.0% vs 64.9% ( p = 0.000) respectively. The rates of NF-κB positive nuclei in the control group and COVID-19 group were 13.4% vs 51.4% ( p = 0.000) in the lung and 38.2% vs 59.3% ( p = 0.000) in the spleen. The rates of HMGB-1 positive cytoplasm in the control and the COVID-19 group were 19.7% vs 50.3% ( p = 0.000) in the lung and 12.3% vs 45.2% ( p = 0.000) in the spleen. The targets of SARS-CoV-2 are the lung and spleen, where increased macrophages could be involved in the up-regulation of pyroptosis-related inflammatory factors such as NF-κB, HMGB-1, NLRP3, IL-18, and GSDMD.